Pengaruh Profitabilitas terhadap Nilai Perusahaan dengan Kebijakan Dividen sebagai Variabel Moderasi terhadap Perusahaan Properti dan Real Estate - Tiara Indah Febiyanti; Muhadjir Anwar (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
The value of the company describes the quality of the company's effectiveness in growing the welfare of shareholders and is often used as a company's consideration. This is always tied to the stock price. The implementation of this research is expected to be able to interpret the impact of profitability on company scores and the role of dividend policy variables. The population taken is from companies in the property and real estate division, as many as 14 (fourteen) with a span of 4 years from 2017 and 2020. In this research, the researchers used the classical assumption test analysis method and multiple linear regression analysis. The variable from profitability to company score has an at-score of -1.010 and a significance score of 0.318, an at-count score of dividend policy of 0.322, and a significance score of 0.017. All variables from this research have calculated F of 2,963. This figure exceeds the score from the F table. Profitability has a non-significant effect on the company's score and significant dividend policy and can strengthen the impact of profitability on the value or score of the company. Key Words: SFA, Panel Data, Efficiency Key Words : Dividend Policy; Firm Value; profitability